Diversity pipelines: The rationale to recruit and support minority physicians. Issue 1 (2nd January 2021) - Clayborne, Elizabeth P.; Martin, Daniel R.; Goett, Rebecca R.; Chandrasekaran, Eashwar B.; McGreevy, Jolion
Abstract: Emergency physicians care for patients from all backgrounds with respect and expertise. We aspire to treat everyone equitably and make decisions at the bedside that are not based on age, race, socioeconomic status, gender, sexual orientation, religion, language, or any other category. In many settings, there is a stark contrast between the diversity of our patient populations and that of the physicians caring for them. Despite our intention to minimize the effects of implicit and explicit bias, when the physician workforce does not reflect the patient population, there may be significant assumptions, mistrust, and misunderstandings between people from different backgrounds. As medical professionals, increasing the diversity of our workforce and support for programs and policies that increase underrepresented minority (URM) physicians in emergency medicine is important. Increasing URM physicians will not only improve the quality of care for our patients, but also the quality of education and training in our profession. It is crucial that we prioritize pipeline programs that recruit and support URM physicians. This article describes the rationale to increase diversity within the profession of emergency medicine and the essential mechanisms to achieve this goal. In the same way that we hold individuals accountable to a clinical standard of care, we should hold our institutions to an organizational standard of diversity.